Molar teeth impaction on panoramic radiography - Fudhla, Fitri Hanifah; Sudjana, Nuskah; Riawan, Lucky (Padjadjaran Journal of Dentistry, 2015)
Introduction: The third molar are the most frequently impacted tooth. Characteristic of impacted third molar in every person may be different. Third molar are the last erupted tooth in dental arch and grow during the final period of growth, therefore third molar have the most potential for problems. The aim of this research are to know and to give description about third molar impaction based on the jaw location, classification, and complaint. Methods: This research was a retrospective observasional descriptive research. Population of this study are students of Dentistry Faculty of Padjadjaran University from class 2008.The sampling was incidentale. A total of 45 panoramic radiograph and the complaint questionaires based on pathological condition that associated with third molar impacted were observed. Classifications that used in this research were Pell and Gregory for the mandible, and Archer and Kruger for the maxilla. Results: This research shows that 62,8% of third molar are impacted. Based on jaw location, the third molar impaction most frequently occurs in the mandible (66,35%) and region 4 (33,65%). In the mandible, 81,58% are bilateral, 42,03% are mesioangular, 55,07% are IIB Pell and Gregory classification. In the maxilla, 60% are C position Archer and Kruger classification, 65,71% are sinus approximation, and 40% are mesioangular similar with distoangular. The most frequent complaint from pathological condition that associated with third molar impacted is local pain at third molar area (75,6%). Conclusion: Third molar impaction most frequently occur in the mandible with mesioangular and IIB Pell and Gregory classification as the most frequently classification. The most frequent complaint from pathological condition that associated with third molar impacted is local pain at third molar area.